Transformation of Creative Economy Based on Home Industry to Encourage Family Resilience and Increase Community Income - Rachmawaty Kadir; Musakirawati; Masetya Mukti (CV. Sakura Digital Nusantara, 2023)
This research aims to explain the creative economic development based on home industry carried out by EcoNatural Society Foundation, explain its impact on community income, and supporting factors in creative economic development at EcoNatural Society Foundation. The method used is descriptive qualitative research, the way data is collected is through observation, interviews, and documentation of the object of research. The data analysis technique uses descriptive analysis. The results showed (1) the development of a home industry-based creative economy carried out by the EcoNatural Society Foundation through the formation of household business groups, (2) an increase in the income of people participating in household business groups, (3) internal and external factors that support the development carried out by the EcoNatural Society Foundation in Selayar Islands Regency.